PENERAPAN PENDIDIKAN MATEMATIKA REALISTIK INDONESIA (PMRI) UNTUK MENINGKATKAN HASIL BELAJAR MATEMATIKA SISWA KELAS III SD NEGERI 46 PEKANBARU - Eni Trihoti; Gustimal Witri; Otang Kurniaman (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2017)
Abstract: This research is motivated by the facts found in class 3 SDN 46 Pekanbaru, which shows the results of learning mathematics is still relatively low. formulation of the problem in this research is